L'héritage d'Ahmadou Kourouma dans la littérature contemporaine francophone: le cas de Léonora Miano - Outeirinho, Maria de Fátima (2014)
Jean-Michel Djian remarked in his biography on Ahmadou Kourouma (2010): "On aurait dit que les Mabanckou, Waberi, Koua-Zotti, Léonora Miano, Kossi Efoui, Fatou Diome, pour n'en citer qu'une petite poignée, attendaient que Kourouma clôture d'une oeuvre magistrale un siècle désenchanté, pour qu'enfin ses 'enfants' s'autorisent à ouvrir une nouvelle page littéraire délivrée des scories d'une Afrique épuisée par ses propres ressentiments". In fact, Leonora Miano's writing is indebted to a postcolonial discourse such as Kourouma contributions. Often placed under labels such as those related to the new generation of Migritude or new generation of writers "qui se nourrit tout autant de la culture du pays d'accueil que de celle du pays d'origine" (Volet 2008), Léonora Miano pays attention particularly to issues that cross border identities rooted on African European or Western affiliations, pointing to recenterings on broader spectrum, which includes Africa, Europe and America. Therefore in this paper we aim to reflect on the extensions and variations from Ahamadou Kourouma's legacy, regarding the issue of the duty of remembrance - especially in terms of the slave trade, Independences and post-colonialism -, the discourse about shared responsibility for the outcomes of contemporary Africa in order to better build its relationship to the world and better conceive being in the world resulting from multiple belongings.